Elaboración y aplicación de un manual de educación sexual para los niños y niñas de 5 a 6 años de edad de la escuela “Elvira Ortega” en la parroquia La Matriz, provincia de Cotopaxi en el período 2009 – 2010 - Carvajal Palacios, Alicia Elizabeth (2015)
Sex education is responsibility of everyone who is in contact with the boy and the girl, like parents and educators with their attitude and relationship they transmit consciously or unconsciously sexual patterns. We must provide healthy and truthful information to boys and girls, when they will feel curios and when they will ask for information. Parents occupy immediately and for future an important role in the psychosexual development of the child. The sexual attitudes of the parents influence in the primary sexuality of the children, so the feelings about their own body are a source of pleasure that gets a self-image through which it follows that is enjoyable and can be loved by others.